Prior exposure strongly influences mechanisms underpinning survival of heat shock in Escherichia coli - Yasir, Muhammad; Turner, A. Keith; Bastkowski, Sarah; Jarvis, Caroline S.; Sweet, Ryan; Truong, Megan; Charles, Ian G.; Webber, Mark A. (Frontiers in Microbiology, 2025)
The heat shock response of Escherichia coli represents a canonical example of how bacteria can recognize a stress and invoke a protective response by altering specific gene regulation. However, most understanding of the processes involved arises from experiments where cells have been subjected to immediate heat shock. In this study, we identified the populations of transposon mutants in E. coli BW25113 involved in response to sudden heat shock and stepwise heat stress conditions. We used Transposon-Directed Insertion Site Sequencing with expression (TraDIS-Xpress) to identify genes whose function or expression contributed to survival under 5 different heat conditions. These conditions included direct exposure to 44°C, 47°C, or 50° C referred to as “heat shock” or half an hour exposure at 44°C, followed by exposure to 47°C or 50°C referred to as “stepwise heat stress”.A total of 530 genes were identified as contributing to one or more of the heat stress conditions tested, including known heat shock resistance genes. Only 8 genes were common to all 5 conditions, with 4 of these 8 genes being associated with energy generation. The results showed fundamentally different responses between shock and stepwise stress. In heat shock conditions, most genes conferring a fitness benefit contained an increase in insertions (loss of function) as compared to the control (37°C), while in stepwise heat stress, most genes conferring a fitness benefit had fewer insertions (representing protection of function) as compared to the control. Cell envelope genes involved in lipopolysaccharide biosynthesis (lpxM, lptC), the Tol-Pal system (tolABQR-pal), and outer membrane biogenesis (BAM complex) were detrimental during heat shock but essential for stepwise adaptation, while regulatory genes relA (stringent response) and the rsx operon (redox regulation) were specifically required for stepwise heat stress response.Prior exposure to sub-lethal heat stress dramatically alters the genetic landscape for survival, allowing energy-intensive adaptive responses rather than the cellular simplification strategies required during immediate heat shock. This work shows that stress responses are dependent on stepwise heat exposure whilst providing significant new information about the sudden heat shock.